A New In Vitro Model to Evaluate Anti-Adhesive Effect against Fungal Nail Infections - Paola Perugini; Margherita Bonetti; Marta Guerini; Giorgio Musitelli; Pietro Grisoli (Applied Sciences, 2021)
Nail fungal infection is often mistakenly considered a minor issue or a purely esthetic problem that is not worth solving. However, onychomycosis has been demonstrated to have a negative impact on a patient’s social life. Therefore, given the poor efficacy of various therapy types, there is strong interest in exploring new methods for evaluating antifungal treatments. As such, the aim of this work was to develop a new protocol, using bovine hoof membranes as a model of the human nail to evaluate the capability of a product claiming to prevent fungal adhesion, which is the first step of the infection. In this work, two specific and representative fungal strains, Trichophyton rubrum and Candida albicans, were used. In order to evaluate the possible protective activity of a product against fungal contamination of the nail plate, it was first necessary to test the affinity of the hoof membranes to be contaminated by the fungi. Then, a pharmaceutical product and a base coat were tested as a positive and negative control, respectively, by introducing the membranes (anti-fungal, basic or no treatment and single vs. multiple treatments) into the fungal suspensions for three different contact times (15 min, 5 h and 24 h). The results showed that the more significant antiadhesive effect (AE) was obtained against Trichophyton rubrum than against Candida albicans. Furthermore, taking into account the results obtained at all testing times, 5 h appeared to be the best time for testing the antiadhesive activity. The results obtained after three treatments with drugs and on washed membranes, in comparison to one single application of antifungal product (AP), demonstrated clearly that the drug was able to penetrate deeper into the membranes to exert itself, even after washing and also after only 15 min of contact. Thus, hoof membrane has been shown to be a valuable in vitro model for this kind of product assessment.